Method for impregnating fibrous materials with an optimized system for resupplying and cleaning fine particles

By maintaining the powder level and mass constant in the fluidized bed, combined with the scraper and suction system, the problems of fiber misalignment and powder agglomeration during the pre-impregnation of the fibrous material are solved, and uniform impregnation and fluidized bed of the fibrous material are achieved The stability of quality improves production efficiency and safety.

CN114761192BActive Publication Date: 2024-12-24ARKEMA FRANCE SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080084555.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-06
Filing Date
2020-11-05
Publication Date
2024-12-24
Estimated Expiration
2040-11-05

AI Technical Summary

Technical Problem

The prior art has fiber misalignment and mechanical deterioration in the pre-impregnation process of fibrous materials, resulting in fiber damage, uneven distribution and agglomeration of powder particles, affecting the quality of the fluidized bed and impregnation effect, and the flight of fine particles leads to the material. Loss and operational safety issues.

Method used

By keeping the level and mass of the powder in the fluidized bed basically constant, using a scraper and a lateral suction system to prevent powder agglomeration and fiber breakage, ensuring uniform distribution of powder particles and impregnation quality, the dry pre-impregnation process and tension device are used to prevent powder clumping and damage. Fiber spread.

Benefits of technology

It realizes uniform impregnation of fibrous materials, improves the quality and production efficiency of fluidized beds, reduces material losses and operating risks, and ensures the stability of pre-impregnation quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761192B_ABST
    Figure CN114761192B_ABST
Patent Text Reader

Abstract

A method for producing an impregnated fibrous material comprising at least one fibrous material made of continuous fibers and at least one thermoplastic polymer matrix comprises a step of pre-impregnating the fibrous material with a thermoplastic polymer matrix in powder form, characterized in that the pre-impregnation step is carried out dry in a tank (20) comprising a fluidized bed (22), the pre-impregnation step being carried out while keeping the level h of the powder present in the tank (20) and the mass m of the powder substantially constant, the level h being from hi to hi-3%, in particular hi-2%, during the implementation of the pre-impregnation step, wherein hi is the initial level of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step, and the mass m being from mi to mi±0.5%, wherein mi is the initial mass of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a process for producing an impregnated cellulosic material comprising at least one cellulosic material made of continuous fibers and at least one thermoplastic polymer matrix, said process comprising a step of pre-impregnating said cellulosic material with the thermoplastic polymer matrix in powder form in a fluidized bed, the level h of said powder present in a tank (20) and the mass m of said powder being kept substantially constant in the tank (20) during the implementation of the pre-impregnation step.

[0002] In other words, during the implementation of the pre-impregnation step, the level h of the powder is from h i to h i -3%, especially h i -2%,h i is the initial level of the powder in the tank (20) at the beginning of the pre-impregnation step, and during the pre-impregnation step the mass m is increased from m i To m i ±0.5%, m i is the initial mass of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step.

[0003] In this specification, the expression "fibrous material" is understood to mean an aggregate of reinforcing fibers. Before the shaping of the fibrous material, it is in the form of roving. After its shaping, it is in the form of a ribbon (or tape), a strip or a sheet. Their aggregate constitutes a unidirectional reinforcement or a fabric or a nonwoven (NCF).

[0004] In this specification, the term "strip" is used to denote a strip of fibrous material having a width greater than or equal to 400 mm. The term "strip" is used to denote a strip having a calibrated width less than or equal to 400 mm.

[0005] The quality of the impregnation of reinforcing fibers with thermoplastic polymers, in particular high-viscosity thermoplastic polymers, for the production of thermoplastic pre-impregnated tapes requires perfect control of the amount of impregnated polymer and the quality of the distribution of the polymer within the rovings of reinforcing fibers during the impregnation process. Many patents or patent applications, such as WO 2018 / 229114, WO 2018 / 234436, WO 2018 / 234439 and EP 2788408, describe the fact that the spreading of the fibers is an essential parameter for obtaining a uniform quality of polymer impregnation within the fibers on the final tape.

[0006] Usually, the spreading of reinforcing fibers such as carbon fibers is produced via mechanical, pneumatic and / or vibration systems. The main drawbacks of these methods are the generation of fiber dislocations within the roving (spreading by blowing or suction) and / or mechanical degradation of the fibers due to the application of too high transverse stresses.

[0007] Whatever the system used, the spread produced can produce breakage of the fibers or at least partial deterioration of these fibers. A fiber fluff called "hair" is then formed. The hair (usually composed of several accumulated fiber fragments) is mainly produced at the contact points between the fibers and the impregnation line elements (guide pins, support rollers, etc.). The greater the mechanical stress applied, the more hair tends to be produced. Hair is then observed over time, which is produced and eventually accumulates, especially in the pre-impregnation bath. In fluidized bed type pre-impregnation baths, hair locally deteriorates the fluidization quality and the fluidized bed quality continuously decreases. As a result, the level of the fluidized bed decreases and the local concentration of powder particles changes. An uneven powder bath is then observed that no longer allows correct and continuous impregnation during the process. The amount of powder captured by the fiber roving and therefore the amount of polymer impregnated in the belt tends to decrease over time.

[0008] Agglomeration of powder particles is also observed, which can occur in blind spots and does not come from the accumulation of hair. It is well known to the person skilled in the art that due to the stalling of the powder in contact with the can wall, all the powder eventually settles in the corners, in particular the corners of the can, resulting in agglomeration. In addition, due to the contact between them and their generally not perfectly spherical geometry, the powders also eventually agglomerate and therefore settle. Therefore, this has an overall effect on the level of the powder in the can and therefore reduces it.

[0009] Document FR 2 659 595 describes a process for impregnating fibers by aerosol supplied with a powder through a fluidized bed comprising a system for reintroducing previously introduced, but not impregnated, particles of powder intentionally electrostatically charged.

[0010] Document EP 0 246 167 describes a process for impregnating fibers by aerosol, in which the volume or weight of the fibers and of the polymer entrained is maintained at a preselected value.

[0011] Document WO 2018 / 234436 describes an electrostatic process for impregnating fibers.

[0012] The particle sizes used in fluidized bed prepreg processes for powders are generally concentrated in the range of 100-200 μm, with relatively large deviations (D10 and D90 are far from D50) (see in particular documents WO2018115737A1 and WO2018115738A1). This dispersion is necessary to obtain a uniform and stable fluidization, as well as an optimized prepreg quality. Due to the high gap in size between the smallest particles (a few μm in diameter or fine particles) and the largest particles (e.g. up to 500-600 μm), fine particles fly away from the fluidizing tank (20) (more than 99% by volume of the powder that flies away has a size of 0.01 μm-60 μm). The flying away of these fine particles leads to several main problems:

[0013] impoverishment of the fluidized bed in terms of fine particles, which can lead to changes in the pre-impregnation quality of the fiber rovings and in the stability of the fluidized bath and its level,

[0014] Significant loss of material and therefore a reduction in the profitability of the manufacturing process. It is preferred to be able to capture the fine particles and upgrade them,

[0015] Flyaway of fine particles (<10 μm) causes QHSE (Quality, Health, Safety and Environment) issues for operators and equipment.

[0016] Similarly, during production, the prepreg tank (20) must be replenished with a "stock solution" of the same composition as that initially introduced into the prepreg bath. In a fluidized bed system, it is therefore necessary to maintain not only a constant powder height but also a constant powder mass in the fluidizing tank (20) in order to obtain a product that is well impregnated and constant in terms of polymer content. The replenishment of powder is usually done manually and regularly, causing small but very current changes in the composition of the bath during production time.

[0017] Therefore, the various problems listed above must be solved.

[0018] The invention therefore relates to a process for producing an impregnated cellulosic material comprising at least one cellulosic material made of continuous fibers and at least one thermoplastic polymer matrix, said process comprising a step of pre-impregnating said cellulosic material with the thermoplastic polymer matrix in powder form, characterized in that said pre-impregnation step is carried out dry in a tank (20) comprising a fluidized bed (22), said pre-impregnation step being carried out while keeping the level h of said powder present in the tank (20) and the mass m of said powder substantially constant, said level h varying from h to m during the implementation of the pre-impregnation step. i to h i -3%, especially h i -2%, of which h iis the initial level of the powder in the tank (20) at the beginning of the pre-impregnation step, and during the pre-impregnation step the mass m is increased from m i To m i ±0.5%, where m i is the initial mass of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step.

[0019] The pre-impregnation step is carried out while the level h and the mass m of the powder remain substantially constant, which is essential in the process of the invention.

[0020] In practice, at the beginning of the pre-impregnation step, when fluidization begins, there is an initial height h in the tank (20). i or an initial level of fluidized powder and an initial mass m in the tank (20) i of powder.

[0021] During the implementation of the pre-impregnation step, both the level of powder present in the tank (20) and the mass of the powder must remain substantially constant, i.e., in the tank (20) during the implementation of the pre-impregnation step, the level h must continue to remain substantially constant; in other words, the level h must be from h i to h i -3%, especially h i -2%, of which h i is the initial level of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step, and the mass of the powder must be kept substantially constant continuously; in other words, during the implementation of the pre-impregnation step the mass m must be increased from m i To m i ±0.5%, where m i is the initial mass of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step.

[0022] Initial level of powder h i It can be measured according to various techniques known to those skilled in the art of using fluidized beds of powders.

[0023] For example, it can be measured by means of sensors, in particular membrane-type position sensors, or by means of ultrasonic position measurement, for example sold by Flowline Inc. (USA) or even by means of laser measurement of the level of the fluidized bed in the tank, for example the laser displacement sensors sold by Keyence (France) or by means of continuous level measurement and level detection devices sold by Endress and Hauser (France).

[0024] If necessary, an averaging of the measurement results in the region of the fluidized bed actually used for pre-impregnation of the fibers can be performed.

[0025] According to FR2659595 and EP0246167, the fluidized bed has a horizontal surface like a liquid in a container.

[0026] The initial level of powder along the length and width of the fluidised bed can therefore be easily measured.

[0027] Advantageously, the surface of the fluidized bed used in the present invention is horizontal, in particular like the liquid in the container.

[0028] Advantageously, the height of the fluidized bed is constant across the width and length of the tank.

[0029] Using an automatic system for powder replenishment of the tank based on gravimetric metering devices connected to a scale on which the fluidizing tank rests and to the fluidized bed level sensors, a constant mass of powder in the fluidized bed can be obtained to maintain a constant prepreg quality over time. These metering devices feed the fluidizing tank continuously in an unused area of ​​the tank so as not to disturb the process.

[0030] Advantageously, during the implementation of the pre-impregnation step, the level h must be from h i to h i -2%, and the mass m must be from m i To m i ±0.5%.

[0031] In one embodiment, the volume average diameter D50 of the thermoplastic polymer powder particles is 30-300 μm, in particular 50-200 μm, more particularly 70-200 μm.

[0032] The volume diameters (D10, D50 and D90) of the thermoplastic polymer powder particles are defined according to standard ISO 9276:2014.

[0033] "D50" corresponds to the volume mean diameter, ie the value of the particle size which divides the particle population under consideration exactly in half.

[0034] "D90" corresponds to the value at 90% of the cumulative curve of the volume particle size distribution.

[0035] "D10" corresponds to the size of 10% of the volume of the particles.

[0036] In one embodiment, the tank (20) is replenished with a thermoplastic polymer matrix in powder form to compensate for the consumption of said thermoplastic polymer matrix due to the pre-impregnation of said fibrous material.

[0037] In one embodiment, the particle size of the powder in the tank (20) is substantially constant, ie the D50 varies by a maximum of +20%.

[0038] In another embodiment, the particle size of the fine particles of the powder in the tank (20) is substantially constant, ie the D10 varies by a maximum of +30%.

[0039] In yet another embodiment, the particle size of the large particles of the powder in the tank (20) is substantially constant, ie the D90 varies by a maximum of +10%.

[0040] Advantageously, the particle size of the powder in the tank (20) is substantially constant, ie the D50 varies by a maximum of +20%, and the particle size of the fine particles of the powder in the tank (20) is substantially constant, ie the D10 varies by a maximum of +30%.

[0041] Advantageously, the particle size of the powder in the tank (20) is substantially constant, ie the D50 varies by a maximum of +20%, and the particle size of the large particles of the powder in the tank (20) is substantially constant, ie the D90 varies by a maximum of +10%.

[0042] Advantageously, the particle size of the large particles of the powder in the tank (20) is substantially constant, i.e. the D90 varies by a maximum of +10%, and the particle size of the fine particles of the powder in the tank (20) is substantially constant, i.e. the D10 varies by a maximum of +30%.

[0043] Advantageously, the particle size of the powder in the tank (20) is substantially constant, i.e. the D50 varies by a maximum of +20%, and the particle size of the fine particles of the powder in the tank (20) is substantially constant, i.e. the D10 varies by a maximum of +30%, and the particle size of the large particles of the powder in the tank (20) is substantially constant, i.e. the D90 varies by a maximum of +10%.

[0044] When the fibrous material enters the fluidized bed, the powder of the thermoplastic polymer matrix present in the tank (20) initially settles on the fibrous material and is therefore consumed during pre-impregnation, which results in a decrease in the level of powder in the tank (20) and a decrease in the quality of the powder present in the tank (20). The level and quality present in the tank (20) must therefore be compensated by introducing a "reserve ingredient", i.e. an initial thermoplastic polymer matrix in powder form (i.e. having the same D10, D50 and D90 properties).

[0045] However, with fluidization, fine particles initially present in the "reserve ingredient" leave the fluidized bed and the tank (20), causing the D50, D10 and D90 of the "reserve ingredient" to change, even if the level and quality present in the tank (20) are compensated by introducing the "reserve ingredient" into the tank (20).

[0046] D50 and / or D90 and / or D10 must therefore be kept constant.

[0047] In one embodiment, the tank (20) comprises a fluidized bed (22) and the pre-impregnation step is performed as the roving (81a) or rovings are simultaneously spread between an inlet and an outlet of the fluidized bed (22).

[0048] The term "spreading" means the factor that causes the width of the fibrous material (or roving) to increase relative to its initial width l (i.e. when it enters the system), thus ensuring the pre-impregnation step. Quite obviously, it is the average width of the roving when flattened over several spools (whether it is its initial width or its width after spreading), determined by averaging the measurements obtained without contact (laser, LED, etc.). The initial width does not necessarily correspond to the width of the roving at the outlet of the fibrous material supply reel.

[0049] In one embodiment, the tank (20) is equipped with a scraper.

[0050] As mentioned above, whatever the system used, the spreading produces breakage of the fiber filaments: "hair" is then formed, which accumulates over time, especially in the pre-impregnation bath, thus locally deteriorating the fluidization quality. The quality of the fluidized bed is constantly deteriorating.

[0051] In addition, agglomeration of the powder particles themselves occurs, especially in the dead zones of the fluidized bed. Due to both the filaments and the "natural" agglomeration of the powder, the level of the fluidized bed is generally reduced and the local concentration of the powder particles changes. Therefore, a scraper is needed to break up the accumulated powder lumps and thereby resuspend the powder particles.

[0052] In one embodiment, when the level h <h i -3%, especially h <h i -2% when the scraper is automatically used.

[0053] In order to obtain a substantially constant level of the fluidized bed in order to maintain a substantially constant prepreg quality over time, a scraper system is automatically and periodically activated when the threshold of the fluidized bed drops below a critical level. The purpose of this scraper is to dislodge filaments in unused areas of the fluidizing tank and to break up powder that has accumulated in areas of the tank that are not very turbulent (a phenomenon known to those skilled in the art of fluidization). It can take several physical forms: fragments of individual fibers a few mm or cm in length, continuous fibers that roll up on themselves to form small balls, clusters of continuous short fibers in the form of suspended matter, lumps of agglomerated powder, etc.

[0054] In one embodiment, the tank (20) is equipped with a transverse suction system which sucks fine particles having a diameter of 0.01-60 μm which leave the tank (20) during fluidization.

[0055] Advantageously, 99% of the fine particles exiting the tank (20) during fluidization have a diameter of 0.01-60 μm.

[0056] The diameter of the particles leaving the tank can be measured by conventional techniques known to those skilled in the art (eg laser particle size measurement over several production runs on powder that has flown away and been collected and then analyzed).

[0057] In another embodiment, the tank (20) is equipped with a transverse suction system which sucks fine particles with a D50 of 0.01-60 μm leaving the tank (20) during fluidization.

[0058] Advantageously, the aspirated particles are continuously reintroduced into the tank (20).

[0059] In addition to the natural consumption of powder due to the pre-impregnation step, the formation of filaments and the formation of lumps of agglomerated powder, fine particles of the "reserve ingredients" also fly away above the fluidizing tank and will therefore cause changes in the D50, D10 and D90 of the "reserve ingredients", which will disturb the quality, uniformity and amount of pre-impregnation of the fibrous material and reduce the level of the fluidized bed despite the introduction of the "reserve ingredients".

[0060] The fine particles are composed of particles having a diameter of 0.01 to 60 μm.

[0061] No particles having a diameter smaller than 0.01 μm were initially present in the system.

[0062] Particles having a diameter greater than 60 μm generally did not fly away over the tank.

[0063] It is therefore necessary to recover the fine particles having a diameter of 0.01-60 μm which leave the tank ( 20 ) during fluidization and then reintroduce them into the tank.

[0064] Advantageously, the lateral suction system is equipped with a selection screen to prevent particles larger than 60 μm from being sucked in and reintroduced into the tank.

[0065] The "stock content" of powder added to the tank may also contain some of the particles recovered by the suction / recovery system, depending on their particle size.

[0066] Advantageously, the tank (20) is equipped with: a scraper; and a transverse suction system which sucks fine particles having a diameter of 0.01-60 μm out of the tank (20).

[0067] Advantageously, 99% of the fine particles exiting the tank (20) during fluidization have a diameter of 0.01-60 μm.

[0068] Advantageously, the tank (20) is equipped with: a scraper; and a transverse suction system which sucks fine particles with a D50 of 0.01-60 μm leaving the tank (20).

[0069] About the Pre-preg Step

[0070] Examples of units for implementing the manufacturing process are described in the international application WO 2015 / 121583 and are shown in addition to the tank (also called prepreg tank, which in the present case comprises a fluidized bed equipped with tensioning means (which may be press rollers)). Figure 1 middle.

[0071] The pre-impregnation step and the tensioning device may be as described in WO 2018 / 115737.

[0072] The pressure rollers may be stationary or rotating.

[0073] The pre-impregnation step of the fibrous material is carried out by passing one or more rovings through a continuous pre-impregnation device comprising a tank (20) which in particular comprises a fluidized bed (22) of polymer powder.

[0074] The polymer powder or polymer is suspended in a gas G (for example air) which is introduced into the tank and flows into the tank through a hopper 21. Through this fluidized bed 22 the roving(s) are flowed (circulated).

[0075] The tank may have any shape, in particular cylindrical or parallelepiped, in particular cuboid or cube, advantageously cuboid.

[0076] The tank may be an open or closed tank. Advantageously, it is open.

[0077] In the case where the tank is closed, it is then equipped with a sealing system so that the polymer powder cannot leave the tank.

[0078] The pre-impregnation step is therefore carried out by a dry route, ie the thermoplastic polymer matrix is ​​in powder form (especially suspended in a gas, in particular air), but not dispersible in a solvent or in water.

[0079] Each roving to be pre-impregnated is unrolled from a device (10) having a reel (11) under a tension generated by a reel (not shown). Preferably, the device (10) comprises a plurality of reels (11), each of which makes it possible to unroll a roving to be impregnated. Thus, several fiber rovings can be pre-impregnated simultaneously. Each reel (11) is provided with a brake (not shown) to apply tension to each fiber roving. In this case, an alignment module (12) makes it possible to position the fiber rovings parallel to each other. In this way, the fiber rovings cannot come into contact with each other, which makes it possible to prevent mechanical degradation of the fibers due to friction against themselves.

[0080] The fiber roving or the plurality of parallel fiber rovings then pass through a tank (20) which in particular comprises a fluidized bed (22) and is provided with a tensioning device which is arranged at Figure 1 In the case of a pressure roller (23), the fiber roving or the plurality of parallel fiber rovings then leave the tank after impregnation after a controlled residence time in the powder.

[0081] Controlling the residence time in the powder allows the fibrous material to be pre-impregnated with the thermoplastic polymer matrix with a well-controlled resin content and uniformity.

[0082] The use of at least one tensioning device allows the impregnation to be improved compared to prior art processes, in particular the impregnation is a complete impregnation.

[0083] Tensioning device is understood to mean any system on which the roving has the possibility of running through the tank.The tensioning device may have any shape as long as the roving can run on it.

[0084] The impregnation is performed so that the polymer powder is able to penetrate to the core of the fiber rovings and adhere to the fibers sufficiently to withstand the transportation of the powder coated rovings out of the tank. The powder impregnated roving (one or more) is then sent to a heated calendering device, which may be preheated before calendering and optionally heated after calendering.

[0085] Optionally, the pre-impregnation step can be completed by a step of covering the pre-impregnated roving or rovings just at the outlet of the tank (20) for pre-impregnation with powder in the fluidized bed (22) and just before the calendering step. Thus, the outlet airlock of the tank (20) (fluidized bed 22) can be connected to a covering device (30) which can include a covering crosshead, as also described in patent EP 0 406 067. The covering polymer can be the same or different from the fluidized bed polymer powder. Preferably, it is of the same type. Such covering makes it possible not only to complete the fiber pre-impregnation step in order to obtain a final volume content of polymer within the desired range and avoid the presence of locally too high a fiber content at the surface of the pre-impregnated rovings (which is detrimental to the welding of the tapes during the manufacture of the composite part, in particular to obtain a so-called "ready-to-use" fibrous material of good quality), but also to improve the properties of the composite material obtained.

[0086] The process of the present invention as shown above is carried out by a dry route and without the use of an intentionally charged electrostatic process.

[0087] The expression "using intentional charging" means that a potential difference is applied between the fibrous material and the powder. In particular, the charge is controlled and amplified. The particles of the powder then impregnate the fibrous material by attraction of the charged powder to the fibers. The powder can be charged (negatively or positively) and the fibers charged in the opposite way (positively or negatively) by various means (potential difference between two metal electrodes, mechanical friction on metal parts, etc.).

[0088] The process of the invention does not exclude the presence of electrostatic charges which may arise due to the friction of the fibrous material on elements of the implementation unit before or during its passage in the tank, but which are in any case unintentional charges.

[0089] Advantageously, the content of fibres in the impregnated fibrous material is between 45% and 65% by volume, preferably between 50% and 60% by volume, in particular between 54% and 60% by volume.

[0090] Below 45% fiber, the enhancement of mechanical properties is not significant.

[0091] Above 65%, the limits of the process are reached and mechanical properties are lost again.

[0092] If the fibrous material, such as glass fiber, has a size, an optional desizing step may be performed before the fibrous material passes to the tank. The term "sizing" refers to a surface treatment applied to the reinforcing fibers (fabric sizing); and woven fabrics (plastic sizing) leaving the spinneret.

[0093] The "fabric" sizing applied to the filaments leaving the spinneret consists in depositing a binder which ensures cohesion of the filaments to each other, reduces abrasion and facilitates subsequent processing operations (weaving, hot sheet drape forming, knitting) and prevents the formation of electrostatic charges.

[0094] The "plastic" sizing or "finishing" applied to woven fabrics consists in depositing a bridging agent whose function is to ensure the physicochemical bond between the fiber and the resin and to protect the fiber from its environment.

[0095] Advantageously, the content of fibers in the impregnated fibrous material is 50% to 60% by volume, in particular 54% to 60% by volume.

[0096] Advantageously, the residence time in the powder is between 0.01 s and 10 s, preferentially between 0.1 s and 5 s, and in particular between 0.1 s and 3 s.

[0097] This residence time of the fibrous material in the powder is necessary for the impregnation, in particular complete impregnation, of the fibrous material.

[0098] Below 0.1s, the immersion does not really reach the core.

[0099] Beyond 10 s, the amount of polymer matrix impregnating the fibrous material is too large and the mechanical properties of the pre-impregnated fibrous material will be poor.

[0100] Advantageously, the process of the invention uses a tank comprising a fluidized bed and said pre-impregnation step is carried out with said roving or rovings being spread simultaneously between an inlet and an outlet of said fluidized bed.

[0101] The expression "inlet of the fluidized bed" corresponds to a vertical tangent to one edge of the tank comprising the fluidized bed.

[0102] The expression "outlet of the fluidized bed" corresponds to a vertical tangent to the other edge of the tank comprising the fluidized bed.

[0103] Depending on the geometry of the tank, the distance between its inlet and outlet thus corresponds to: the diameter in the case of a cylinder, the side in the case of a cube, or the width or length in the case of a cuboid. Spreading consists in singulating as much as possible the constituent filaments of the roving from the other filaments surrounding them in their immediate space. It corresponds to the transverse spread of the roving.

[0104] In other words, the transverse spread or width of the roving increases between the inlet of the fluidized bed (or a tank comprising the fluidized bed) and the outlet of the fluidized bed (or a tank comprising the fluidized bed) and thus enables an improved impregnation, in particular a complete impregnation, of the fibrous material.

[0105] The fluidized bed may be open or closed, in particular it is open.

[0106] Advantageously, the fluidized bed comprises at least one tensioning device, said roving or rovings being in contact with a part or the whole of the surface of said at least one tensioning device.

[0107] Figure 2 Details are given of a tank (20) comprising a fluidised bed (22) and a tensioning device (82) of adjustable height.

[0108] The roving (81a) corresponds to the roving before impregnation, which is in contact with part or all of the surface of the at least one tensioning device and therefore runs partly or completely on the surface of the tensioning device (82), the system being immersed in the fluidized bed in which the impregnation takes place. The roving then leaves the tank after a controlled residence time in the powder.

[0109] The rovings (81a) may or may not be in contact with the edge (83a) of the tank (which may be a rotating or fixed roller or a parallelepiped edge).

[0110] Advantageously, said rovings (81a) are optionally in contact with the edge (83a) of the tank.

[0111] Advantageously, the edge (83b) of the tank is a roller, in particular a cylindrical and rotating roller.

[0112] The rovings (81b) may or may not be in contact with the edge (83b) of the tank, which may be a roller, in particular a cylindrical and rotating or fixed roller, or a parallelepiped edge.

[0113] Advantageously, said rovings (81b) are in contact with the edge (83b) of the tank.

[0114] Advantageously, the edge (83b) of the tank is a roller, in particular a cylindrical and rotating roller.

[0115] Advantageously, the roving (81a) is in contact with the edge (83a) of the tank and the edge (83b) of the tank is a roller, in particular a cylindrical and rotating roller and the roving (81b) is in contact with the edge (83b) of the tank and the edge (83b) of the tank is a roller, in particular a cylindrical and rotating roller.

[0116] Advantageously, said tensioning means is perpendicular to the direction of said roving or said rovings.

[0117] Advantageously, said spreading of said roving or said rovings is carried out at least at level with said at least one tensioning device.

[0118] The spreading of the roving thus takes place primarily in level with the tensioning device, but also in level with the edge or edges of the tank if there is contact between the roving and said edge.

[0119] In another embodiment, the at least one tensioning device is a pressure roller of convex, concave or cylindrical shape.

[0120] A convex shape is conducive to spreading, while a concave shape is not conducive to spreading, although spreading can occur.

[0121] The expression “pressing roller” means that the running roving partially or completely presses against the surface of the pressing roller, which results in spreading of the roving.

[0122] Advantageously, said at least one pressing roller is cylindrical in shape and the spread percentage of said roving or rovings between the inlet and the outlet of said fluidized bed is 1%-400%, preferably 30%-400%, preferably 30%-150%, preferably 50%-150%.

[0123] The spread depends on the fiber material used. For example, the spread of carbon fiber material is much greater than that of flax fiber.

[0124] Spreading also depends on the number of fibers or filaments in the roving, their average diameter and their agglomeration due to sizing.

[0125] The diameter of the at least one pressing roller is 3 mm-500 mm, preferably 10 mm-100 mm, in particular 20 mm-60 mm.

[0126] Below 3 mm, the deformation of the fiber caused by the pressure roller is too great.

[0127] Advantageously, the pressure roller is cylindrical and non-grooved and is in particular made of metal.

[0128] When the tensioning means is at least one roller, according to a first variant, there is a single roller in the fluidized bed and the impregnation is carried out at an angle α1 formed by the roving or rovings between the start of the roller and a vertical tangent to the roller.

[0129] The angle α1 formed by the roving or rovings between the starting position of the roller and the vertical tangent of the roller makes it possible to form a zone in which the powder concentrates, resulting in a "corner effect" which, together with the simultaneous spreading of the rovings by the roller, makes it possible to impregnate over a greater roving width than in the prior art techniques and thus improve impregnation. In combination with a controlled residence time, complete impregnation is achieved.

[0130] Advantageously, the angle α1 is 0-89°, preferably 5°-85°, preferably 5°-45°, preferably 5°-30°.

[0131] However, an angle α1 of 0-5° can create a risk of mechanical stresses which would lead to breakage of the fibres and an angle α1 of 85°-89° does not create sufficient mechanical stresses to produce the “angle effect”.

[0132] Thus, a value of the angle α1 equal to 0° corresponds to a vertical fiber. It is quite obvious that the height of the cylindrical pressing roller is adjustable so as to make it possible to place the fiber vertically.

[0133] It would not be outside the scope of the invention to perforate the wall of the tank to be able to allow the roving to escape.

[0134] Advantageously, the edge (83a) of the tank is equipped with rollers, in particular cylindrical and rotating rollers, over which the roving or rovings run, causing a prior spreading.

[0135] Advantageously, downstream of the tank comprising the fluidized bed there are one or more tensioning devices on which spreading is induced.

[0136] Advantageously, spreading is initiated on said tensioning device(s) defined above and continues on the edge (83a) of the tank.

[0137] After passing over the pressure roller(s), the spread is then at a maximum.

[0138] Figure 2 An embodiment with a single roller is described without limitation, wherein the tank (20) comprises a fluidized bed (22) in which there is a single cylindrical roller. The angle α1 is the angle formed between a vertical tangent to the roller and the roving in contact with said roller.

[0139] Arrows on the fibers indicate the direction of travel of the fibers.

[0140] Advantageously, the level of the powder in the fluidised bed is at least half way up the press rollers.

[0141] It is quite obvious that the "angle effect" caused by the angle α1 favours impregnation on one face, but the spreading of the roving obtained by the rollers also makes it possible to have impregnation on the other face of the roving. In other words, at the angle α1 formed by the roving or rovings between the starting position of the at least one roller R1 and the vertical tangent to the roller R1, the impregnation is facilitated on one face of the roving or rovings, but the spreading also makes it possible to impregnate the other face.

[0142] The angle α1 is as defined above.

[0143] About fibrous materials

[0144] As regards the fibres constituting the fibrous material, these are in particular fibres of mineral, organic or vegetable origin. Among the fibres of mineral origin, mention may be made, for example, of carbon fibres, glass fibres, silicon fibres, basalt or basalt-based fibres, or silica fibres.

[0145] Among the fibers of organic origin, mention may be made of fibers based on thermoplastic or thermosetting polymers, such as semiaromatic polyamide fibers, aramid fibers or polyolefin fibers.

[0146] Preferably, they are based on amorphous thermoplastic polymers and have a glass transition temperature Tg that is higher than the Tg of the thermoplastic polymer or polymer blend constituting the prepreg matrix when the latter is amorphous, or higher than the Tm of the thermoplastic polymer or polymer blend constituting the prepreg matrix when the latter is semicrystalline. Advantageously, they are based on semicrystalline thermoplastic polymers and have a melting temperature Tm that is higher than the Tg of the thermoplastic polymer or polymer blend constituting the prepreg matrix when the latter is amorphous, or higher than the Tm of the thermoplastic polymer or polymer blend constituting the prepreg matrix when the latter is semicrystalline. Thus, there is no risk of melting of the organic fibers constituting the cellulosic material during impregnation by the thermoplastic matrix of the final composite.

[0147] Among the fibers of plant origin, mention may be made of natural fibers based on flax, hemp, lignin, bamboo, (raw) silk, especially spider silk, sisal, and other cellulosic fibers, in particular viscose fibers. These fibers of plant origin can be used pure, treated or coated with a coating to promote adhesion and impregnation of the thermoplastic polymer matrix.

[0148] The fibrous material may also be a cloth knitted or woven (woven) with fibers.

[0149] It may also correspond to a fiber with a supporting yarn.

[0150] These constituent fibers can be used individually or as a mixture.Thus, organic fibers can be mixed with mineral fibers to be pre-impregnated with thermoplastic polymers and form a pre-impregnated fibrous material.

[0151] Preferably, the fibrous material is formed by continuous fibers of carbon, glass or silicon carbide or a mixture thereof, in particular carbon fibers. It is used in the form of one roving or a plurality of rovings.

[0152] In the impregnated material, also referred to as "ready-to-use" material, the impregnated thermoplastic polymer or polymer blend is uniformly and evenly distributed around the fibers. In this type of material, the impregnated thermoplastic polymer must be distributed as evenly as possible within the fibers to obtain a minimum amount of porosity, i.e., a minimum amount of space between the fibers. In particular, the presence of pores in this type of material can act as stress concentration points when under, for example, mechanical tensile stress, and it then forms a failure initiation point for the impregnated fibrous material and mechanically weakens it. Therefore, the uniform distribution of the polymer or polymer blend improves the mechanical strength and uniformity of the composite material formed by these impregnated fibrous materials.

[0153] Thus, in the case of so-called "ready-to-use" impregnated material, the content of fibers in the impregnated fibrous material is 45% to 65% by volume, preferably 50% to 60% by volume, in particular 54% to 60% by volume.

[0154] The degree of impregnation can be measured by image analysis of a cross section of the strip (in particular using a microscope or a camera or a digital camera), by dividing the surface area of ​​the strip impregnated with the polymer by the total surface area of ​​the product (impregnated surface area plus the surface area of ​​the pores). In order to obtain good quality images, the strip cut across its transverse direction is preferably coated with a standard polishing resin and polished using a standard protocol that enables the sample to be observed with a microscope at a magnification of at least 6 times.

[0155] Advantageously, the impregnated fibrous material has a degree of porosity of less than 10%, in particular less than 5%, in particular less than 2%.

[0156] It should be noted that a porosity level of zero is difficult to achieve and therefore, advantageously, the porosity level is greater than 0% but less than the levels noted above.

[0157] The degree of porosity corresponds to the degree of closed pores and can be determined by electron microscopy or, as described in the present examples section, as the relative deviation between the theoretical density and the experimental density of the impregnated fibrous material.

[0158] The fibers that may be part of the composition of the fibrous material may have different linear basis weights or titles or titrations or "tex" and / or be present in different quantities in the roving. Thus, the most commonly used rovings consist of 600-4800 tex for glass fibers and 3000 (3K), 6000 (6K), 12000 (12K), 24 000 (24K), 48 000 (48K), 50000 (50K) or 400 000 (400K) fibers for carbon fibers. Carbon fibers typically have a diameter close to 7-8 μm and glass fibers have a diameter of, for example, about 13, 15, 17 or 20 μm.

[0159] It is quite obvious that the spreading depends on the number of fibers present in the fibrous material or roving.

[0160] Thus, for 12K roving the spread represents 2-3 times the initial width l, for 24K roving the spread represents 2-4 times the initial width l and for 50K roving the spread represents 1.5-2.5 times the initial width l.

[0161] Thermoplastic polymers of the matrix

[0162] Thermoplastics, or thermoplastic polymers, are understood to mean materials which are generally solid at ambient temperature, which may be semicrystalline or amorphous and which soften during temperature increase, in particular after exceeding their glass transition temperature (Tg), and flow at higher temperatures when they are amorphous, or which, when they are semicrystalline, may exhibit pronounced melting above their melting temperature (Tm) and become solid again when the temperature drops below their crystallization temperature (for semicrystalline polymers) and below their glass transition temperature (for amorphous polymers).

[0163] Tg and Tm are determined by differential scanning calorimetry (DSC) according to standards 11357-2:2013 and 11357-3:2013, respectively.

[0164] As regards the polymer constituting the matrix for pre-impregnating the fibrous material, this is advantageously a thermoplastic polymer or a thermoplastic polymer blend. The thermoplastic polymer or polymer blend may be ground into powder form in order to be able to use it in an apparatus such as a tank, in particular a fluidized bed tank, or in an aqueous dispersion.

[0165] The apparatus, in particular in the form of a tank, a fluidized bed tank, may be open or closed.

[0166] Optionally, the thermoplastic polymer or thermoplastic polymer blend further comprises a carbon-based filler, in particular carbon black or a carbon-based nanofiller, preferably selected from carbon-based nanofillers, in particular graphene and / or carbon nanotubes and / or carbon nanofibrils, or mixtures thereof. These fillers make it possible to conduct electricity and heat and therefore make it possible to promote the melting of the polymer matrix when the polymer matrix is ​​heated.

[0167] Optionally, the thermoplastic polymer comprises at least one additive, in particular chosen from catalysts, antioxidants, heat stabilizers, UV stabilizers, light stabilizers, lubricants, fillers, plasticizers, flame retardants, nucleating agents, chain extenders and dyes, electrical conductors, thermal conductors, or mixtures of these.

[0168] Advantageously, the additive is selected from flame retardants, electrical conductive agents and thermal conductive agents.

[0169] According to another variant, the thermoplastic polymer or thermoplastic polymer blend may further comprise a liquid crystal polymer or a cyclic polybutylene terephthalate, or a mixture containing the same, such as the CBT100 resin sold by Cyclics Corporation. These compounds make it possible in particular to fluidize the polymer matrix in the molten state, so as to better penetrate into the core of the fibers. Depending on the nature of the polymer or thermoplastic polymer blend used to produce the prepreg matrix, in particular its melting temperature, one or the other of these compounds will be chosen.

[0170] The thermoplastic polymer introduced into the composition of the pre-impregnated matrix of fibrous material may be chosen from:

[0171] - polymers and copolymers from the following classes: aliphatic or cycloaliphatic polyamides (PA) or semiaromatic PA (also known as polyphthalamides (PPA), polyphthalamide),

[0172] -PEBA,

[0173] - polyureas, in particular aromatic polyureas,

[0174] - polymers and copolymers from the class of acrylic resins, such as polyacrylates, and more particularly polymethyl methacrylate (PMMA) or its derivatives,

[0175] - polymers and copolymers of the class of poly(aryletherketone) (PAEK) such as poly(etheretherketone) (PEEK), or poly(aryletherketoneketone) (PAEKK) such as poly(etherketoneketone) (PEKK), or derivatives thereof,

[0176] - aromatic polyetherimide (PEI),

[0177] - polyarylene sulfide, in particular polyphenylene sulfide (PPS),

[0178] - polyaryl sulfones, in particular polyphenyl sulfone (PPSU, polyphenylene sulfone),

[0179] - polyolefins, in particular polypropylene (PP),

[0180] - Polylactic acid (PLA),

[0181] - Polyvinyl alcohol (PVA),

[0182] - fluorinated polymers, in particular poly(vinylidene fluoride) (PVDF) or polytetrafluoroethylene (PTFE) or polychlorotrifluoroethylene (PCTFE),

[0183] and their blends.

[0184] Advantageously, when the polymer is a blend of two polymers P1 and P2, the weight ratio of polymers P1 and P2 is 1-99% to 99-1%.

[0185] Advantageously, when the thermoplastic polymer is a blend and the prepreg process uses a dry powder, the blend is in the form of a powder obtained by "dry mixing" before introduction into the prepreg tank, either by "dry mixing" carried out directly in the tank or by grinding of the compound previously carried out in an extruder.

[0186] Advantageously, this blend consists of a powder obtained by “dry mixing” before introduction into the tank or directly in the tank, and this blend of the two polymers P1 and P2 is a blend of PEKK and PEI.

[0187] Advantageously, the PEKK / PEI blend is 90-10% to 60-40% by weight, in particular 90-10% to 70-30% by weight.

[0188] The thermoplastic polymer may correspond to a non-reactive final polymer that will impregnate the cellulosic material, or to a reactive prepolymer that will also impregnate the cellulosic material but, depending on the chain ends it has, will be able to react with itself or with another prepolymer after preimpregnation, or with a chain extender, and in particular during heating in an oven at the level of a tensioning device and / or during processing of the tape in the final process for manufacturing a composite part.

[0189] The expression "non-reactive polymer" means a polymer whose molecular weight is no longer likely to change significantly when it is processed, ie whose number-average molecular weight (Mn) changes by less than 50% and which therefore corresponds to the final polyamide polymer of the thermoplastic matrix.

[0190] In contrast, the expression "reactive polymer" means that during processing the molecular weight of the reactive polymer will change by reaction of the reactive prepolymers with each other by condensation or substitution or with chain extenders by polyaddition and without elimination of volatile by-products, to give the final polyamide polymer (non-reactive) of the thermoplastic matrix.

[0191] According to a first possibility, the prepolymer may comprise or consist of at least one reactive prepolymer (polyamide) having two terminal functional groups X' and Y' on the same chain (i.e. on the same prepolymer), which are respectively co-reactive with each other by condensation, more particularly X' and Y' are respectively amine and carboxyl, or carboxyl and amine. According to a second possibility, the prepolymer may comprise or consist of at least two polyamide prepolymers that are reactive with each other and each of which has the same two terminal functional groups X' or Y', respectively (same for the same prepolymer and different between the two prepolymers), the functional group X' of one prepolymer being capable of reacting only with the functional group Y' of the other prepolymer, in particular by condensation, more particularly wherein X' and Y' are respectively amine and carboxyl, or carboxyl and amine.

[0192] According to a third possibility, the prepolymer may comprise or consist of: at least one prepolymer of the thermoplastic polyamide polymer having n reactive terminal functional groups X, the reactive terminal functional groups X being chosen from: -NH2, -CO2H and -OH, preferably NH2 and -CO2H, wherein n is 1-3, preferably 1-2, more preferentially 1 or 2, more particularly 2; and at least one chain extender Y-A'-Y, wherein A' is a hydrocarbon divalent radical carrying 2 identical reactive terminal functional groups Y (the reactive terminal functional groups Y having reactivity by addition polymerization with at least one functional group X of the prepolymer a1), preferably having a molecular weight of less than 500 and more preferentially less than 400.

[0193] The number average molecular weight Mn of the final polymer of the thermoplastic matrix is ​​preferably within a range extending from 10 000 to 40 000, preferably from 12 000 to 30 000. These Mn values ​​may correspond to an intrinsic viscosity greater than or equal to 0.8, measured in m-cresol according to standard ISO 307:2007, but with a change of solvent (m-cresol is used instead of sulfuric acid and the temperature is 20° C.).

[0194] The reactive prepolymers according to the above two options have a number average molecular weight Mn ranging from 500 to 10 000, preferably from 1000 to 6800, in particular from 2500 to 6800.

[0195] Mn is determined in particular on the basis of: the content of terminal functional groups determined by potentiometric titration in solution; and the functionality of the prepolymer. The molecular weight Mn can also be determined by size exclusion chromatography or by NMR.

[0196] The nomenclature used to define polyamides is described in the standard ISO 1874-1:2011 “Plastics—Polyamide (PA) moulding and extrusion materials—Part 1: Designation”, in particular on page 3 (Tables 1 and 2), and is well known to the person skilled in the art.

[0197] The polyamide may be a homopolyamide or a copolyamide or a blend thereof.

[0198] Advantageously, the prepolymer constituting the matrix is ​​chosen from: polyamide (PA), in particular from aliphatic polyamides, cycloaliphatic polyamides, and semiaromatic polyamides (polyphthalamides) (which are optionally modified by urea moieties), and copolymers thereof; polymethyl methacrylate (PPMA) and copolymers thereof; polyetherimide (PEI); polyphenylene sulfide (PPS); polyphenylene sulfone (PPSU); PVDF; poly(etherketoneketone) (PEKK); poly(etheretherketone) (PEEK); fluoropolymers such as poly(vinylidene fluoride) (PVDF).

[0199] For the fluoropolymer, a homopolymer of vinylidene fluoride (VDF, which has the formula CH2=CF2) or a copolymer of VDF comprising at least 50% by weight of VDF and at least one other monomer copolymerizable with VDF can be used. The content of VDF must be greater than 80% by weight, or even better 90% by weight, to ensure good mechanical strength and chemical resistance of the structural part, especially when it is subjected to thermal and chemical stresses. The comonomer can be a fluorine-containing monomer such as vinyl fluoride (vinyl fluoride).

[0200] For structural parts that have to withstand high temperatures, in addition to the fluoropolymers described, it is also advantageous according to the invention to use PA, PAEK (polyaryletherketone) having a high glass transition temperature Tg, such as poly(etherketone) (PEK), poly(etheretherketone) (PEEK), poly(etherketoneketone) (PEKK) or poly(etherketoneetherketoneketone) (PEKEKK).

[0201] Advantageously, the thermoplastic polymer is a polymer having a glass transition temperature such that Tg ≥ 80°C, especially ≥ 100°C, in particular ≥ 120°C, especially ≥ 140°C, or a semicrystalline polymer having a melting temperature Tm ≥ 150°C.

[0202] Advantageously, said thermoplastic polymer of said matrix is ​​a non-reactive thermoplastic polymer.

[0203] Advantageously, said at least one thermoplastic prepolymer is chosen from polyamides, PEKK, PEI, and blends of PEKK and PEI.

[0204] Advantageously, the polyamide is chosen from aliphatic polyamides, cycloaliphatic polyamides and semiaromatic polyamides (polyphthalamides).

[0205] Advantageously, the aliphatic polyamide prepolymer is selected from:

[0206] - polyamide 6 (PA6), polyamide 11 (PA11), polyamide 12 (PA12), polyamide 66 (PA66), polyamide 46 (PA46), polyamide 610 (PA610), polyamide 612 (PA612), polyamide 1010 (PA1010), polyamide 1012 (PA1012), polyamide 11 / 1010 and polyamide 12 / 1010, or blends thereof or copolyamides thereof, and block copolymers, in particular polyamide / polyether (PEBA), and the semiaromatic polyamide is a semiaromatic polyamide optionally modified by urea moieties, in particular PA MXD6 and PA MXD10 or a semiaromatic polyamide of formula X / YAr (as described in EP 1 505 099), in particular a semiaromatic polyamide of formula A / XT, wherein A is selected from a moiety derived from an amino acid, a moiety derived from a lactam and a moiety corresponding to the formula (Ca diamine).(Cb diacid), wherein a represents the number of carbon atoms of the diamine and b represents the number of carbon atoms of the diacid, a and b are each 4-36, advantageously 9-18, the (Ca diamine) moiety is selected from a linear or branched aliphatic diamine, alicyclic diamine and alkyl aromatic diamine and the (Cb diacid) moiety is selected from a linear or branched aliphatic diacid, alicyclic diacid and aromatic diacid;

[0207] XT represents a moiety obtained by the polycondensation of a Cx diamine and terephthalic acid, wherein x represents the number of carbon atoms of the Cx diamine, x being from 6 to 36, advantageously from 9 to 18; in particular a polyamide of the formula A / 6T, A / 9T, A / 10T or A / 11T, A being as defined above; in particular polyamides PA 6 / 6T, PA 66 / 6T, PA 6I / 6T, PA MPMDT / 6T, PA PA11 / 10T, PA 11 / 6T / 10T, PAMXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA BACT / 10T / 11, PABACT / 6T / 11.

[0208] T corresponds to terephthalic acid, MXD to meta-xylylenediamine (meta-xylylenediamine), MPMD to methylpentamethylenediamine and BAC to bis(aminomethyl)cyclohexane.

[0209] Advantageously, the thermoplastic polymer is a semi-aromatic polyamide.

[0210] Advantageously, the thermoplastic polymer is a semiaromatic polyamide chosen from PA MPMDT / 6T, PA PA11 / 10T, PA 11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA BACT / 10T / 11, PA BACT / 6T / 11. About the pre-impregnation step:

[0211] As already indicated above the pre-impregnation step is carried out in a fluidized bed.

[0212] Advantageously, the pre-impregnation is carried out in a fluidized bed and there are one or more tensioning devices (E) upstream of the system.

[0213] A fluidized bed pre-impregnation process is described in WO 2018 / 115736.

[0214] An example of a unit for carrying out a manufacturing process without a heating step by means of at least one tensioning device is described in the international application WO 2015 / 121583.

[0215] This system describes the use of a tank comprising a fluidized bed for the pre-impregnation step and may be used within the scope of the present invention.

[0216] Advantageously, the tank comprising the fluidized bed is provided with at least one tensioning device (E') which may be a pressing roller.

[0217] It should be noted that the tensioning means (E) and (E') may be identical or different, both as regards their material and their shape and characteristics (depending on the shape, diameter, length, width, height, etc.).

[0218] However, the tensioning device (E') is neither a heating device nor is it heated.

[0219] The pre-impregnation step of the fibrous material is carried out by passing one or more rovings through a continuous pre-impregnation device comprising a tank (20) equipped with at least one tensioning device (E') and comprising a fluidized bed (22) of powder of the polymer matrix.

[0220] The polymer matrix or polymer powder is suspended in a gas G (for example air) introduced into the tank and flowing into the tank (20) through a hopper (21). The roving(s) are streamed (circulated) through the fluidized bed (22).

[0221] The tank may have any shape, in particular cylindrical or parallelepiped, in particular cuboid or cube, advantageously cuboid.

[0222] The tank (20) may be an open or closed tank. Advantageously, it is open.

[0223] In the case where the can is closed, it is equipped with a sealing system so that the powder of the polymer matrix cannot leave the can.

[0224] The pre-impregnation step is therefore carried out by a dry route, ie the thermoplastic polymer matrix is ​​in powder form (especially suspended in a gas, in particular air), but not dispersible in a solvent or in water.

[0225] Each roving to be pre-impregnated enters a tank (20) after passing over a tensioning device (E).

[0226] The fiber roving or the plurality of parallel fiber rovings then enter a tank (20) which in particular comprises a fluidized bed (22) equipped with at least one tensioning device (E') as a pressure roller or is already present in a tank and then enters a fluidized bed (22) equipped with at least one tensioning device (E').

[0227] After optionally controlling the residence time in the powder, the fiber roving or parallel fiber rovings then leave the tank after pre-impregnation.

[0228] In one embodiment, the process according to the invention comprises the step of heating the pre-impregnated fibrous material in order to melt the thermoplastic polymer of the matrix and to effect the impregnation of the fibrous material.

[0229] The heating step may be performed as described in WO 2018 / 234439:

[0230] The first heating step may immediately follow the pre-impregnation step, or other steps may occur between the pre-impregnation step and the heating step.

[0231] Advantageously, said first heating step follows immediately after the pre-impregnation step. The expression "follows immediately after" means that there is no intermediate step between the pre-impregnation step and said heating step.

[0232] Advantageously, a single heating step is carried out immediately after the pre-impregnation step.

[0233] Advantageously, said at least one heating system is selected from infrared lamps, UV lamps and convection heating.

[0234] Since the fibrous material is in contact with the tensioning device(s) in the heating system, and the tensioning devices are conductive, the heating system is also by conduction.

[0235] Advantageously, said at least one heating system is chosen from infrared lamps.

[0236] Advantageously, said at least one tensioning device (E") is a pressing roller of convex, concave or cylindrical shape.

[0237] It should be noted that the pressing rollers corresponding to the tensioning means (E), (E') and (E'') can be identical or different both in terms of their material and shape and their characteristics (diameter, length, width, height, etc. depending on the shape).

[0238] A convex shape is conducive to spreading, while a concave shape is not conducive to spreading, although spreading can occur.

[0239] The at least one tensioning device (E") may also have a shape that alternates between convex and concave. In this case, the running of the roving over a roller of convex shape causes the spreading of said roving, and then the running of the roving over a roller of concave shape causes the retreat of the roving, and so on, so that, if necessary, the uniformity of the impregnation, in particular of the core, can be improved.

[0240] The expression “pressing roller” means that the running roving partially or completely presses against the surface of the pressing roller, which causes the roving to spread.

[0241] The rollers may be free (rotating) or fixed.

[0242] They may be smooth, ribbed (angular), or grooved.

[0243] Advantageously, the roller is cylindrical and ribbed. When the roller is ribbed, there may be two ribs in opposite directions from the center of the roller, allowing the roving to move away towards the outside of the roller, or two ribs in opposite directions from the outside of the roller, making it possible to bring the locks towards the center of the roller.

[0244] This heating step makes it possible to make the pre-impregnation homogeneous, so as to complete the impregnation and so as to have a core impregnation and a high fiber volume content (which is in particular constant in at least 70% of the volume of the strip or strip, in particular at least 80% of the volume of the strip or strip, in particular at least 90% of the volume of the strip or strip, more in particular at least 95% of the volume of the strip or strip), and to reduce the porosity.

[0245] The spread depends on the fiber material used. For example, the spread of carbon fiber material is much greater than that of flax fiber.

[0246] Spreading also depends on the number of fibers in the roving, their average diameter and their agglomeration due to sizing.

[0247] The diameter of the at least one pressing roller (tensioning device (E")) is 3 mm - 100 mm, preferably 3 mm - 20 mm, in particular 5 mm - 10 mm.

[0248] Below 3 mm, the deformation of the fiber caused by the pressure roller is too great.

[0249] Advantageously, the pressure roller is cylindrical and non-grooved and is in particular made of metal.

[0250] Advantageously, said at least one tensioning device (E") is constituted by at least one pressing roller of cylindrical shape.

[0251] Advantageously, said at least one tensioning device (E") is constituted by 1-15 rollers (R1R15), preferably 3-15 rollers (R3-R15), in particular 6-10 rollers (R6-R10), of cylindrical shape.

[0252] It is quite obvious that, whatever the number of tensioning devices (E") present, they are all located or comprised in the environment of the heating system, ie they are not external to the heating system.

[0253] According to another aspect, the invention relates to the use of a process as defined above for producing a calibrated strip suitable for producing a three-dimensional composite part by automated placement of said strip using an automatic machine.

[0254] Advantageously, the composite components relate to the following fields: transport, in particular motor vehicle transport, oil and gas, in particular offshore oil and gas, hydrogen, gas storage, in particular hydrogen, aviation, maritime and rail transport; renewable energy, in particular wind turbines or hydro turbines, energy storage devices, solar panels; thermal protection panels; sports and leisure, health and medicine, and electronic equipment.

[0255] According to another aspect, the invention relates to a three-dimensional composite part, characterised in that it results from the use of a process as defined above.

[0256] According to a further aspect, the invention relates to a tank (20) for use in a process as defined above, comprising a fluidized bed (22), a scraper or a transverse suction system for suctioning the fine particles.

[0257] According to a further aspect, the invention relates to a tank (20) for use in a process as defined above, comprising a fluidized bed (22), a scraper and a transverse suction system for suctioning the fine particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0258] [ Figure 1 ] presents a partial diagram of an implementation unit of a manufacturing process for pre-impregnated fibrous materials according to WO 2018 / 115736.

[0259] [ Figure 2 ] presents a tank comprising a fluidized bed, provided with at least one tensioning device (E') which may be a pressure roller.

[0260] [ Figure 3 ] presents a photograph of a jar with a scraper.

[0261] [ Figure 4 ] is a diagram of an automated scraper system for lint and for spreading powder over time. Lint is automatically recovered in an unused area of ​​the tank (which does not disturb the rest of the tank). Figure 4 and Figure 5 It is just one picture, but for visibility reasons it has been split into two parts; Figure 4 represents the left part and Figure 5 Indicates the right part.

[0262] [ Figure 5 ] is the right part as explained above.

[0263] [ Figure 6 ] presents a cyclone separator making it possible to recover the powder sucked above the fluidized bed.

[0264] [ Figure 7 ] shows the level of the fluidized bed and the decrease in the weight percentage of thermoplastic polymer (BACT / 10T) in the cellulosic material AS4 from Hexcel over time. Left scale: bed height

[0265] Right scale: wt. % of thermoplastic polymer (BACT / 10T). Example

[0266] Example 1

[0267] Production trials were carried out on a pilot production line to produce a 3000 mm 3AS4 12k cellulosic material from Hexcel was pre-impregnated with a BACT / 10T thermoplastic polymer matrix having a particle size of D50=106 μm in a transparent parallelepiped tank, with powder only added manually as the pre-impregnation proceeded. The particle size of the added powder was equal to the particle size in the tank at the beginning. This situation is therefore a worst case scenario, in which nothing is controlled or readjusted with respect to the particle size.

[0268] The following 4 types of powders were obtained, and their particle sizes can be analyzed:

[0269] - powder carried away by the fibrous material and having a particle size distribution substantially equal to that of the powder present in the tank → G0

[0270] - Powder that flies away and falls down back to the side of the tank and powder that is carried along by the fibrous material and falls from the fibrous material before melting → G1

[0271] - Powder initially present in the tank → G2

[0272] - Powder present in the tank at the end of production → G3

[0273] After 1 week of production, the volume of powder of particle size G1 found next to the can was measured to be equal to 1 / 20 of the volume of powder initially present in the can.

[0274] After 1 week of production, the following table was thus obtained:

[0275] [Table 1]

[0276]

[0277] In the case of recirculation, a G4 particle size is obtained in the tank, which is substantially equal to G0.

[0278] Example 2

[0279] The tank has an automated scraper and an automatic system for supplying powder during production.

[0280] Fiber material: Carbon fiber AS4 12k from Hexcel

[0281] Thermoplastic polymer: BACT / 10T (mol percent 40 / 60) having a Tg of 140°C and a particle size D50 = 106 μm.

[0282] Raking with a scraper every 15 minutes made it possible to restore the initial bed height and the amount of BACT / 10T carried away was maintained for 1 h 40 without adding powder, making it possible to recover the hair produced and deposited at the surface of the frit.

[0283] The results are shown in Figure 7 middle.

Claims

1. Process for producing an impregnated cellulosic material comprising at least one cellulosic material made of continuous fibers and at least one thermoplastic polymer matrix, said process comprising a step of pre-impregnating said cellulosic material with a thermoplastic polymer matrix in powder form, characterized in that said pre-impregnation step is carried out dry in a tank (20) comprising a fluidized bed (22), said pre-impregnation step being carried out while keeping the level h of said powder present in the tank (20) and the mass m of said powder substantially constant, said level h varying from h to m during the implementation of the pre-impregnation step. i to h i -3%, of which h i is the initial level of the powder in the tank (20) at the beginning of the pre-impregnation step, and during the pre-impregnation step the mass m is increased from m i To m i ±0.5%, where m i is the initial mass of the powder in the tank (20) at the beginning of the implementation of the pre-impregnation step, This does not include any electrostatic process using intentional charging.

2. A process as claimed in claim 1, characterised in that during the implementation of the pre-impregnation step the level h is from h i to h i -2%, of which h i is the initial level of said powder in said tank (20) at the beginning of the implementation of the pre-impregnation step.

3. A process as claimed in any one of claims 1 and 2, characterised in that the volume mean diameter D50 of the thermoplastic polymer powder particles is in the range of 30 to 300 μm.

4. A process as claimed in any one of claims 1 and 2, characterised in that the volume mean diameter D50 of the thermoplastic polymer powder particles is in the range of 50 to 200 μm.

5. A process as claimed in any one of claims 1 and 2, characterised in that the volume mean diameter D50 of the thermoplastic polymer powder particles is in the range of 70 to 200 μm.

6. Process as claimed in any one of claims 1 and 2, characterized in that the tank (20) is replenished with a thermoplastic polymer matrix in powder form to compensate for the consumption of said thermoplastic polymer matrix due to the pre-impregnation of said fibrous material.

7. A process as claimed in any one of claims 1 and 2, characterised in that the particle size of the powder in the tank (20) is substantially constant, ie the D50 varies by a maximum of +20%.

8. Process as claimed in any one of claims 1 and 2, characterized in that the particle size of the fine particles of the powder in the tank (20) is substantially constant, ie the D10 varies by a maximum of +30%.

9. A process as claimed in any one of claims 1 and 2, characterised in that the particle size of the large particles of the powder in the tank (20) is substantially constant, ie the D90 varies by a maximum of +10%.

10. A process as claimed in any one of claims 1 and 2, characterized in that the tank (20) comprises a fluidized bed (22) and the pre-impregnation step is carried out with one roving (81a) or more rovings being spread simultaneously between the inlet and the outlet of the fluidized bed (22).

11. Process as claimed in any one of claims 1 and 2, characterised in that the tank (20) is equipped with a scraper.

12. A process as claimed in claim 11, characterised in that when the level h <h i -3%, the scraper is automatically used.

13. A process as claimed in claim 11, characterised in that when the level h <h i -2%, the scraper is automatically used.

14. Process according to any one of claims 1 and 2, characterised in that the tank (20) is equipped with a transverse suction system which sucks fine particles having a diameter of 0.01-60 μm which leave the tank (20) during fluidisation.

15. Process as claimed in claim 14, characterized in that the sucked particles are continuously reintroduced into the tank (20).

16. Process as claimed in any one of claims 1 and 2, characterized in that the tank (20) is equipped with a scraper and a transverse suction system which sucks fine particles having a diameter of 0.01-60 μm out of the tank (20).

17. A process as claimed in claim 10, characterized in that the fluidized bed (22) comprises at least one tensioning device (82), the roving (81a) or the plurality of rovings being in contact with a portion or the entirety of the surface of the at least one tensioning device (82).

18. Process as claimed in claim 17, characterized in that said spreading of said roving (81a) or said rovings is carried out at least at the level of said at least one tensioning device (82).

19. Process as claimed in claim 18, characterized in that the at least one tensioning device (82) is a roller of convex, concave or cylindrical shape.

20. Process as claimed in claim 19, characterized in that said at least one pressing roller is of cylindrical shape and the spread percentage of said roving (81a) or said rovings between the inlet and the outlet of said fluidized bed is between 1% and 400%.

21. Process as claimed in claim 19, characterized in that said at least one pressing roller is of cylindrical shape and the spread percentage of said roving (81a) or said rovings between the inlet and the outlet of said fluidized bed is between 30% and 400%.

22. Process as claimed in claim 19, characterized in that said at least one pressing roller is of cylindrical shape and the spread percentage of said roving (81a) or said rovings between the inlet and the outlet of said fluidized bed is between 30% and 150%.

23. Process as claimed in claim 19, characterized in that said at least one pressing roller is of cylindrical shape and the spread percentage of said roving (81a) or said rovings between the inlet and the outlet of said fluidized bed is between 50% and 150%.

24. A process as claimed in any one of claims 1 and 2, characterised in that the thermoplastic polymer is a non-reactive thermoplastic polymer.

25. A process as claimed in claim 24, characterised in that it comprises the step of heating the pre-impregnated fibrous material in order to melt the thermoplastic polymer and complete the impregnation of the fibrous material.

26. Process as claimed in any one of claims 1 and 2, characterised in that the thermoplastic polymer is a reactive prepolymer which is capable of reacting with itself or with another prepolymer or with a chain extender, depending on the chain ends it has.

27. A process as claimed in claim 26, characterised in that it comprises the steps of heating the pre-impregnated fibrous material to melt and polymerise the thermoplastic prepolymer, optionally together with the chain extender, and to complete the impregnation of the fibrous material.

28. A process as described in any one of claims 1 and 2, characterized in that the at least one thermoplastic polymer is selected from: poly(aryletherketone) (PAEK); poly(aryletherketoneketone) (PAEKK); aromatic polyetherimide (PEI); polyarylsulfone; polyarylsulfide; polyamide (PA); PEBA; polyacrylate; polyolefin; polylactic acid (PLA); polyvinyl alcohol (PVA); and fluoropolymers; and blends thereof.

29. A process as claimed in claim 28, characterised in that the poly(aryletherketone) (PAEK) is a poly(etheretherketone) (PEEK).

30. The process as claimed in claim 28, characterized in that the poly(aryletherketoneketone) (PAEKK) is a poly(etherketoneketone) (PEKK).

31. The process as claimed in claim 28, characterized in that the polyaryl sulfone is polyphenyl sulfone (PPSU).

32. The process as claimed in any one of claims 28, characterized in that the polyarylene sulfide is polyphenylene sulfide (PPS).

33. Process as claimed in claim 28, characterized in that the polyamide (PA) is a semiaromatic polyamide (polyphthalamide type), which is optionally partially modified by urea.

34. A process as claimed in claim 28, characterised in that the polyacrylate is polymethyl methacrylate (PMMA).

35. A process as claimed in claim 28, characterised in that the polyolefin is polypropylene.

36. The process as claimed in claim 28, characterized in that the fluoropolymer is polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE) or polychlorotrifluoroethylene (PCTFE).

37. A process as claimed in claim 28, characterised in that the blend is a blend of PEKK and PEI.

38. A process as claimed in claim 37, characterised in that the blend of PEKK and PEI is a blend of 90-10% by weight to 60-40% by weight of PEKK and PEI.

39. The process as claimed in claim 37, characterized in that the blend of PEKK and PEI is a blend of 90-10% by weight to 70-30% by weight of PEKK and PEI.

40. Process as claimed in any one of claims 1 and 2, characterised in that the at least thermoplastic polymer is a polymer having a glass transition temperature such that Tg ≥ 80°C, or a semi-crystalline polymer having a melting temperature Tm ≥ 150°C.

41. Process as claimed in any one of claims 1 and 2, characterized in that the at least thermoplastic polymer is a polymer having a glass transition temperature such that Tg ≥ 100°C, or a semi-crystalline polymer having a melting temperature Tm ≥ 150°C.

42. Process as claimed in any one of claims 1 and 2, characterized in that the at least thermoplastic polymer is a polymer having a glass transition temperature such that Tg ≥ 120°C, or a semi-crystalline polymer having a melting temperature Tm ≥ 150°C.

43. Process as claimed in any one of claims 1 and 2, characterized in that the at least thermoplastic polymer is a polymer having a glass transition temperature such that Tg ≥ 140°C, or a semi-crystalline polymer having a melting temperature Tm ≥ 150°C.

44. A process as claimed in any one of claims 1 and 2, characterised in that the at least thermoplastic polymer is chosen from polyamides, aliphatic polyamides, cycloaliphatic polyamides and semiaromatic polyamides (polyphthalamides), PEKK, PEI, and blends of PEKK and PEI.

45. A process as claimed in any one of claims 1 and 2, characterised in that the content of fibres in the impregnated fibrous material is between 45% and 65% by volume.

46. ​​A process as claimed in any one of claims 1 and 2, characterised in that the content of fibres in the impregnated fibrous material is between 50% and 60% by volume.

47. A process as claimed in any one of claims 1 and 2, characterised in that the fibre content of the impregnated cellulosic material is between 54% and 60%.

48. A process as claimed in any one of claims 1 and 2, characterised in that the degree of porosity in the impregnated fibrous material is less than 10%.

49. A process as claimed in any one of claims 1 and 2, characterised in that the degree of porosity in the impregnated fibrous material is less than 5%.

50. A process as claimed in any one of claims 1 and 2, characterised in that the degree of porosity in the impregnated fibrous material is less than 2%.

51. A process as claimed in any one of claims 1 and 2, characterised in that the thermoplastic polymer further comprises a carbon-based filler or a mixture thereof.

52. The process as claimed in claim 51, characterized in that the carbon-based filler is carbon black or a carbon-based nanofiller.

53. The process as claimed in claim 51, characterized in that the carbon-based filler is chosen from carbon-based nanofillers.

54. Process as claimed in claim 53, characterized in that the carbon-based nanofillers are graphene and / or carbon nanotubes and / or carbon nanofibrils.

55. A process as claimed in any one of claims 1 and 2, characterised in that the fibrous material comprises continuous fibres selected from the group consisting of carbon fibres; glass fibres; silicon carbide fibres; basalt-based or basalt fibres; silica fibres; natural fibres; or amorphous thermoplastic fibres having a glass transition temperature, Tg, which is higher than the Tg of the polymer or the polymer blend when the polymer or the polymer blend is amorphous, or higher than the Tm of the polymer or the polymer blend when the polymer or the polymer blend is semicrystalline; or semicrystalline thermoplastic fibres having a melting temperature, Tm, which is higher than the Tg of the polymer or the polymer blend when the polymer or the polymer blend is amorphous, or higher than the Tm of the polymer or the polymer blend when the polymer or the polymer blend is semicrystalline; or a mixture of two or more of said fibres.

56. A process as claimed in claim 55, characterised in that the natural fibres are flax or hemp fibres, lignin fibres, bamboo fibres, sisal fibres, silk fibres or cellulose fibres.

57. A process as claimed in claim 56, characterised in that the cellulose fibres are viscose fibres.

58. A process as claimed in claim 55, characterised in that the mixture of two or more of the fibres is a mixture of carbon, glass or silicon carbide fibres.

59. The process as claimed in claim 55, characterized in that the continuous fibers are selected from carbon fibers.

60. Use of a process as defined in any one of claims 1 to 59 for producing a calibrated strip suitable for producing a three-dimensional composite part by automated placement of said strip using an automatic machine.

61. Use as claimed in claim 60, characterized in that the composite component relates to the following fields: transportation, oil and gas, hydrogen, gas storage, aviation, maritime and rail transportation; renewable energy; thermal protection panels; sports and leisure, health and medical, and electronic equipment.

62. Use as claimed in claim 61, characterized in that the transport is motor vehicle transport.

63. The use as claimed in claim 61, characterized in that the oil and gas are offshore oil and gas.

64. Use as claimed in claim 61, characterized in that the gas storage is hydrogen storage.

65. The use as claimed in claim 61, characterized in that the renewable energy source is a wind turbine or a hydro turbine, an energy storage device, or a solar panel renewable energy source.

66. Three-dimensional composite component, characterized in that it results from the use of a process as defined in one of claims 60 to 65.

67. A tank (20) for use in a process as defined in any one of claims 1 to 59, comprising a fluidized bed (22) and a scraper or a transverse suction system for suctioning the fine particles.

68. A tank (20) for use in a process as defined in any one of claims 1 to 59, comprising a fluidized bed (22), a scraper and a transverse suction system for suctioning fine particles.